Ammonium-directed dihydroxylation of 3-aminocyclohex-1-enes: development of a metal-free dihydroxylation protocol. - Aciro, C; Claridge, T; Davies, S; Roberts, P; Russell, A; Thomson, J (2008)
Treatment of 3-aminocyclohex-1-enes with mCPBA in the presence of trichloroacetic acid gives the corresponding 1,2-anti-2,3-syn-1-trichloroacetoxy-2-hydroxy-3-aminocyclohexane with high levels of diastereoselectivity (90% de). This is consistent with a mechanism of oxidation involving hydrogen-bonded delivery of the oxidant by the allylic ammonium ion formed in situ, followed by highly regioselective ring-opening of the intermediate epoxide by trichloroacetic acid. The effect of conformational constraints upon the oxidation reaction is also examined.